The Procedure of Metaphor in the Al-Surah Al-Hood and Younus: أسلوب الاستعارۃ التمثیلیۃ فی السورۃ الھود والیونس - Saleem, Dr. Mufti Muhammad; Ahmad , Dr. Matloob; Adnan Hamid, Dr. Hafiz Muhammad; Hasnain , Mubashar (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This research article “The Procedure of Metaphor in the Al-Surah Al-Hood and Younus” the Holy Quran has employed the vatious rhetoric methods in a way that Arabs have never known before so much, so it was unique and miraculous in its style that the holy quran has employed to explain the meaning that would help in the conveyance of the ideas to the mind of the reader. So Many scholars have paid close attention to the literal figuration and emphasized on it in every era to discover and fond out the literal and eloquent beauties of the semantic embellishment of the holy Quran. In this research Article the researchers has tried his best to find out the Figurative metaphor and its various types in the holy Quran expecially in Sura Hood and Younus. The aim of this research is to sort out the Rhetorical embellishments inside the Holy Quran and its impacts on readers of the holy Quran keeping in view the provision of the related examples of with elaborative statements on the occasions.